Farmer FIRST approach for improving livelihood of pumpkin growers in Odisha - Tripathy, Pradyumna; Behera, Basudev; Malik, Debasish; Behera, Stuti Debapriya (Indian Farming, 2020)
Pumpkin hybrid ‘Vimal’ was raised with best management practices under Farmer FIRST Programme operational at Odisha University of Agriculture and Technology, Bhubaneswar during 2017-18 and 2018-19 in Gobindpur Gram Panchayat in Khordha district of Odisha. Because of the FFP interventions, farmers could produce 120 tonne fruit yield of pumpkin, which fetched them bills worth 5 lakh. The income generated from pumpkin cultivation brought significant improvement in livelihood of farm families in form of food and nutritional security, better health care, education of children and creation of household assets.